Differences in self-discipline between general primary school students and religious-based schools: A comparative study - Mahatmaharti, Rr. Agung Kesna; Dinarti, Siti (International Journal of Trends in Mathematics Education Research, 2024)
Self-discipline is the ability of individuals to control themselves and act in accordance with the values they believe in. This study aims to determine the difference in the level of self-discipline between students in general elementary schools and religious-based elementary schools. This research is a comparative research with quantitative approach. The population in this study were 6th grade elementary and MI students in Jombang Regency. The sampling technique used purposive random sampling with a sample size of 100 students, where 50 students came from general elementary schools or SDN and 50 students came from religious-based elementary schools or MI. The technique used to collect data is a questionnaire. The data obtained were analyzed using descriptive and inferential statistics using the t-test. The results obtained through descriptive analysis show that the average self-discipline character of religious-based elementary school students is higher than the average self-discipline character of general elementary school students. Before hypothesis testing, normality and homogeneity tests were conducted to ensure that the data were normal and homogeneous. The results of data hypothesis testing using t-test obtained Sig (2-tailed) value α (0.045 0.05). These results indicate that there is a significant difference in the level of self-discipline between the two groups of students.